International Ratings of Higher Education Institutions: Analysis of Results Taking Into Account the Profile of Their Educational and Scientific Activities - V. A. Gaisenok; О. A. Naumovich; V. V. Samokhval; V. М. Galynsky (Высшее образование в России)
International university rankings outcomes published in 2019 were analyzed by groups in accordance with university’s education and scientific activities. The authors used the methodology applied in the previous work, where they identified seven core activities: classical universities, technical universities, universities of economics, pedagogical universities, medical universities, agricultural universities, universities of culture and arts. The current analysis gained from the data insight and data comparison for 2013, 2014 and 2019 illustrates systematic dependence of the average grades on the university profile. Leading positions in the ranking are occupied by classical and technical universities. Next in the list are groups of pedagogical, economic and medical universities followed by groups of agrarian universities and universities of culture and arts that remain at similar level. According to the Webometrics Rankings, the universities of the group “Culture and Arts” have dramatically dropped since 2013 and 2014, owing to the increasing weight of science indicators. There was carried out the analysis of the positions taken by the top universities of related groups from all over the world including the European Union, the Eurasian Economic Union and the Republic of Belarus. It is illustrated that Russian universities are in the top of their profile groups within the EAEU. National Research University “Higher School of Economics” which is significantly ahead of other economic universities. Rating results in accordance with the profiles of educational and scientific activities of universities were proposed to submit on an equal basis with the classic world and subject ranking of universities.